Acute large‐vessel occlusion masquerading as traumatic injury - Daniel Boron‐Brenner; Ryan Overberger (Journal of the American College of Emergency Physicians Open)
Abstract A patient presented to an urban level 1 trauma center/accredited thrombectomy‐capable stroke center for evaluation of suspected traumatic injury and was quickly determined to have symptoms suspicious for acute stroke that included dense hemiparesis with preserved mental status. He received a thrombectomy with an eventual return to neurologic baseline and discharge to acute inpatient rehabilitation 14 days after presentation.